Environmental Sustainability of Advanced Structures: A Descriptive and Thematic Analysis - Sarah Elattar; Xiancun Hu; Hamed Golzad; Saeed Banihashemi (Buildings)
This systematic review explores how environmental sustainability is addressed in advanced structural systems that utilize innovative materials and technologies such as lightweight designs, adaptive mechanisms, and energy-efficient components. Despite their growing adoption, significant gaps persist across the design–construction–operation continuum, particularly concerning embodied carbon, energy efficiency, material performance, and long-term durability. A total of 61 peer-reviewed studies published between 2013 and 2025 were identified from Scopus and Google Scholar using the PRISMA methodology. The review employed a dual-method approach: a descriptive analysis to examine literature outlets, publication trends, and the frequency of advanced structural topics such as lightweight systems, long-span designs, form and aesthetics, and structural safety, and a thematic analysis using NVivo 14 software, which identified ten key environmental sustainability themes—carbon emissions, thermal performance, energy efficiency, construction waste, life cycle assessment, green certifications, material use, air quality, site and land use, and green environment. While research interest is expanding, limited studies offer comprehensive assessments of Tensile Membrane Structures (TMSs) or Long Span Structures (LSSs), with key challenges including inadequate material optimization and performance under extreme conditions. This review contributes a novel synthesis of existing knowledge by combining a PRISMA-guided selection, descriptive trend analysis, and thematic coding to identify critical gaps and emerging directions, offering a structured foundation for future research and practical strategies in designing environmentally sustainable advanced structures.